Development of analytics tools for e-learning - Vu, Anh Vinh (2017)
The ubiquity of Learning Analytics as an alternative instrument to traditional education method has surged remarkably ever since the blooming of information technology. The term “Learning Analytics” describe the adoption of various data mining or machine learning techniques in educational field. Plenty of learners and instructors’ data, course contents and feedbacks are used to discover knowledge, insights or patterns of the interested subjects and topics. Popular Learning Management System (LMS) has already integrated this feature but approached differently to diverse targets, some examples are SNAPP or LOCO-Analysis. At Nanyang Technological University Singapore, the current situation requires a “smart” learning system that not only supports operational function of traditional LMS, but also possesses the capability to conjecture student performance, through their constantly changing tracks and study results, hence identify in-need subjects prior to examination.